Parenting in Sex Education for Children in The Use of Smartphone During The Covid-19 Pandemic - Aditiya, Novela; Maemonah, Maemonah; Khoirunisa, Khoirunisa (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Sexual deviant behavior of children often occurs as a result of excessive use of smartphones. That excessive use of smartphones needs to get the attention of parents. Parents' attention in using smartphones could be useful for children in understanding sexual knowledge from an early age because the use of smartphone have much information that is not suitable for the child's development and children's age. The purpose of this study is to determine the sexual education delivered by the parents to children, and to overcome children's sexual behavior due to the use of smartphones. This research uses a descriptive qualitative approach by applying case study. The data information is obtained from observation, interviews, and documentation. The data was obtained from 6 informants consist of parents in grade 3 and grade 6 at SD 7 Koba. The result of this study is parenting sex education for children is delivered in a gradual manner according to the child's growth and development phase. The information provided can support their lives and avoid sexual deviant behavior. Materials that can be provided by parents related to sexual education for elementary school children are intended to protect and defend themselves from crimes that threaten themselves from the negative influence of smartphone. To overcome sexual behavior in using smartphone, it is necessary to limit the duration, supervise, and accompany children in using smartphones.